Melting accelerant as well as preparation and application thereof
By reasonably combining grinding, pro-decomposition and mineralization components, liquid melting promoters are prepared, which solves the problems of cement clinker settling time control, firingability and decomposition thermal efficiency of raw materials, and achieves the effect of reducing coal consumption during cement clinker calcination.
Patent Information
- Application Number
- CN202510033753.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-09
AI Technical Summary
Existing mineralizers cannot take into account the control of cement clinker settling time and the burnability and decomposition heat efficiency of raw materials.
By reasonably combining the grinding components, pro-decomposition components and mineralization components, a liquid melting promoter is prepared, including polyether polyols, polymeric glycerol, sodium gluheptanoate, silver acetate, silver hexafluoroantimate and sodium nitrate.
The melting accelerator can stimulate the activity of cement clinker, promote carbonate decomposition, improve the calcination performance of raw materials, and reduce physical coal consumption during clinker calcination.
Smart Images

Figure BDA0005234934470000031 
Figure BDA0005234934470000051 
Figure BDA0005234934470000061
Abstract
Description
Technical Field
[0001] The invention relates to a cement clinker calcining additive and a preparation method thereof, in particular to a dissolution accelerator and a preparation method thereof and an application thereof in cement clinker calcining. Background Art
[0002] During the calcination of cement clinker, calcium carbonate consumes a lot of heat in its endothermic decomposition. Lowering the decomposition temperature (decomposition heat) of calcium carbonate will be the key to reducing the energy consumption of clinker burning and the total energy consumption of the cement industry.
[0003] Cement mineralizers usually refer to one or more composite substances added during the cement clinker production process, which can improve and promote the decomposition of carbonates, increase the thermal efficiency of decomposition, shorten the formation time of clinker minerals, and improve the burnability of raw materials. The types of mineralizers mainly include: (1) sulfates, such as pyrite, natural gypsum, and phosphogypsum; (2) fluorides, such as fluorite, phosphorus slag, and barite tailings; (3) phosphates, such as apatite and phosphorus industrial slag. Although these mineralizers can reduce the sintering temperature, in order to avoid the introduction of excessive P 2 O 5 This results in reduced clinker strength, prolonged setting time, and limited use of mineralizers. Generally, the amount of P introduced by phosphate mineralizers is controlled. 2 O 5 The content does not exceed 0.5%. The limited amount of mineralizer actually has limited effect on improving the burnability of raw materials and promoting the decomposition of carbonates. Therefore, developing an accelerator that can not only ensure that the strength of cement clinker does not change significantly, but also significantly improve the burnability of raw materials and the thermal efficiency of decomposition has become a technical problem that needs to be solved urgently.
[0004] Polyether polyols and polyglycerol are traditional grinding aids. After addition, they can adjust the rheological properties of ore in the roller press and the surface electrical properties of the ore particles, reduce the viscosity caused by grinding and extrusion, promote the dispersion of particles, prevent the adhesion of ore particles on the grinding media and mill linings, and the agglomeration of ore particles, thereby improving the grinding efficiency. As the amount of adsorption on the surface of the material increases, the wear resistance decreases. When it is fully adsorbed, the wear resistance is the minimum, the surface hardness decreases, and the amount of fine powder increases. The effects of polyether polyols and polyglycerol on the burnability of raw materials and the thermal efficiency of decomposition have not been reported. Summary of the invention
[0005] Purpose of the invention: The purpose of the present invention is to provide a dissolution accelerator to solve the problem that the existing mineralizer cannot take into account both the control of cement clinker setting time and the burnability of raw materials and the decomposition thermal efficiency. Another purpose of the present invention is to propose a preparation method of a dissolution accelerator to solve the problem of how to prepare a dissolution accelerator. The third purpose of the present invention is to propose an application of a dissolution accelerator in the firing of cement clinker to solve the problem of how to calcine and prepare cement clinker.
[0006] Technical solution: The dissolution accelerator described in the present invention comprises the following components in parts by weight: 10-25 parts of a grinding aid, 15-25 parts of a decomposition promoter, 10-20 parts of a mineralizer, and 30-65 parts of water; the grinding aid comprises at least two of polyether polyol, polyglycerol and sodium glucoheptonate, and the decomposition promoter comprises at least two of silver acetate, silver hexafluoroantimonate and sodium nitrate.
[0007] Sodium glucoheptanoate (SGH) has the molecular formula C 7 H 13 NaO 8 , which is a common salt of the seven-membered sugar glucoheptonic acid. It has similar properties to sodium gluconate, but its chelating ability is stronger, 2 to 3 times that of sodium gluconate under the same conditions. It has a strong chelating effect on various metal ions such as calcium ions, aluminum ions, and iron ions in an alkaline environment. It contains a multi-hydroxyl functional group structure and has a strong solid-liquid surface activity. It can be adsorbed on the surface of cement raw material particles to form a solvation adsorption layer, which hinders the contact and coagulation of gel particles in the decomposition furnace and hot air circulation, making the raw material easy to be suspended or boiling in the decomposition furnace, improving the fluidity of the raw material and hot air contact, and indirectly increasing the heat exchange rate between the fuel and the raw material. Adding sodium glucoheptonic acid to the grinding aid component based on polyether polyols and polymerized glycerol not only increases the number and types of hydroxyl functional groups, but also provides good solvation adsorption when the raw material is in the decomposition furnace, increases heat exchange, improves the fluidity of the raw material and hot air contact, and makes better use of the thermal energy of coal.
[0008] The effectiveness of grinding aids also depends on the addition of decomposition promoters. During the decomposition process of carbonate, the powder is in a layered accumulation state. The carbon dioxide decomposed inside the material layer has a small diffusion area, large resistance, and slow speed to the airflow. In addition, the particles inside the material layer are wrapped by the carbon dioxide gas film, the carbon dioxide partial pressure is large, and the decomposition temperature is required to be high. In order to solve the efficiency of carbonate decomposition and increase the decomposition speed, silver acetate, silver hexafluoroantimonate, and sodium nitrate are used as decomposition promoters. These substances are easy to decompose after multiple heat exchanges in the decomposition furnace. The vaporization process promotes the full and uniform dispersion of the gas-solid two phases, disturbs the carbon dioxide gas film layer, forms bubbles and quickly breaks, so that hot air can be inhaled smoothly, the heat transfer efficiency is increased, and the decomposition process of the entire carbonate is promoted. If there is a lack of decomposition promoters, the grinding aid can only be adsorbed on the surface of the powder, and it is difficult to penetrate into the surface of the particle minerals adsorbed inside the cement raw material to form a solvated adsorption layer, which greatly reduces the effect of the grinding aid.
[0009] Preferably, the mineralizer comprises at least one of zinc sulfate and sodium hypochlorite.
[0010] The addition of traditional mineral components can reduce the burning temperature of silicate cement clinker. In an oxidizing atmosphere, zinc sulfate and sodium hypochlorite are introduced. Since they are ionic compounds, they can easily adhere to the surface of the material in the solid phase reaction stage, reduce the temperature of the liquid phase when the clinker is burned, and reduce the viscosity of the liquid phase, thereby reducing the formation temperature of alite, improving the crystal development and formation degree, and promoting C 3 The formation of S can obtain high-quality cement clinker, and the setting time does not change significantly compared with traditional cement clinker.
[0011] Preferably, the mineralizer consists of zinc sulfate and sodium hypochlorite in a mass ratio of 20-40:40-100.
[0012] Preferably, the grinding aid consists of polyether polyol, polymerized glycerol and sodium glucoheptonate in a mass ratio of 20-40:30-70:5-35.
[0013] Preferably, the decomposition promoting agent is composed of silver acetate, silver hexafluoroantimonate and sodium nitrate in a mass ratio of 25-55:10-30:20-60.
[0014] The second aspect of the present invention discloses a method for preparing the above-mentioned melting accelerator, comprising the following steps:
[0015] (1) a grinding aid is prepared by mixing polyether polyol, polyglycerol and sodium glucoheptonic acid; a decomposition promoter is prepared by mixing silver acetate, silver hexafluoroantimonate and sodium nitrate; and a mineralizer is prepared by mixing zinc sulfate and sodium hypochlorite;
[0016] (2) A dissolution accelerator is prepared by mixing a grinding aid, a decomposition promoter, a mineralizer and water in proportion.
[0017] The third aspect of the present invention discloses the use of the above-mentioned dissolution accelerator in the calcination of cement clinker.
[0018] The above application includes the following steps:
[0019] (1) adding the dissolution accelerator into cement raw meal to obtain raw meal powder to be burned;
[0020] (2) The raw material powder to be burned is calcined to obtain cement clinker.
[0021] Preferably, in step (1) of the above application, the amount of the dissolution accelerator added is 1.0-1.2wt‰ of the cement raw material, and the cement raw material is dried white raw material.
[0022] Preferably, in step (2) of the above application, the calcination conditions are calcination at 750-820°C for 15-45 min, and then heating to 1400-1430°C for calcination for 30-60 min.
[0023] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:
[0024] The invention aims at the problem that the mineralizer added in the cement clinker calcining process cannot take into account both the control of cement clinker setting time and the burnability of raw meal and the decomposition thermal efficiency. A liquid type dissolution accelerator with low dosage and stable and uniform efficacy is prepared by reasonably matching a grinding aid component, a decomposition promoting component and a mineralizing component. The accelerator can stimulate the activity of cement clinker, promote carbonate decomposition, improve the burnability of raw meal, and reduce the physical coal consumption in the clinker calcining process. DETAILED DESCRIPTION
[0025] The technical solution of the present invention is further described below.
[0026] Example 1: The composition ratio of a melting accelerator and the preparation method are as follows:
[0027] (1) fully mixing polyether polyol, polyglycerol and sodium glucoheptonic acid in a mass ratio of 30:50:20 to obtain a grinding aid;
[0028] (2) fully mixing silver acetate, silver hexafluoroantimonate and sodium nitrate in a mass ratio of 40:20:40 to obtain a decomposition promoting agent;
[0029] (3) mixing zinc sulfate and sodium hypochlorite at a mass ratio of 30:70 to obtain a mineralizer;
[0030] (4) A dissolution accelerator is prepared by mixing 18 parts of a grinding aid, 20 parts of a decomposition promoter, 15 parts of a mineralizer and 47 parts of water.
[0031] The prepared dissolution accelerator is used in the calcination preparation of cement clinker, and the method is as follows:
[0032] (1) Raw material powder (white raw material) is taken into the kiln and dried at 105° C. for 1 hour. The melting accelerator is added to the white raw material at a rate of 1.2 wt‰ of the white raw material and mixed evenly to obtain raw material powder to be fired. The chemical composition of the white raw material is shown in Table 1.
[0033] Table 1 Chemical composition of white raw material
[0034]
[0035] (2) The raw material powder to be fired is pressed into cement raw material test blocks, dried, and then moved into a high-temperature furnace for calcination at 820°C for 30 minutes. Then, it is quickly moved into a high-temperature furnace and calcined at 1430°C for 45 minutes to obtain cement clinker.
[0036] Example 2: The composition ratio of a melting accelerator and the preparation method are as follows:
[0037] (1) fully mixing polyether polyol, polyglycerol and sodium glucoheptonic acid in a mass ratio of 20:30:5 to obtain a grinding aid;
[0038] (2) fully mixing silver acetate, silver hexafluoroantimonate and sodium nitrate in a mass ratio of 25:10:20 to obtain a decomposition promoting agent;
[0039] (3) mixing zinc sulfate and sodium hypochlorite at a mass ratio of 20:40 to obtain a mineralizer;
[0040] (4) A dissolution accelerator is prepared by mixing 10 parts of a grinding aid, 15 parts of a decomposition promoter, 10 parts of a mineralizer and 30 parts of water.
[0041] The prepared dissolution accelerator is used in the calcination preparation of cement clinker, and the method is as follows:
[0042] (1) Raw material powder (white raw material) is taken into the kiln and dried at 105° C. for 1 hour. The melting accelerator is added to the white raw material at a rate of 1.0 wt‰ of the white raw material and mixed evenly to obtain raw material powder to be fired. The chemical composition of the white raw material is shown in Table 1.
[0043] (2) The raw material powder to be fired is pressed into cement raw material test blocks, dried, and then moved into a high-temperature furnace for calcination at 750°C for 40 minutes, and then quickly moved into a high-temperature furnace for calcination at 1400°C for 60 minutes to obtain cement clinker.
[0044] Example 3: The composition ratio of a melting accelerator and the preparation method are as follows:
[0045] (1) fully mixing polyether polyol, polyglycerol and sodium glucoheptonic acid in a mass ratio of 40:70:35 to obtain a grinding aid;
[0046] (2) fully mixing silver acetate, silver hexafluoroantimonate and sodium nitrate in a mass ratio of 55:30:60 to obtain a decomposition promoting agent;
[0047] (3) mixing zinc sulfate and sodium hypochlorite at a mass ratio of 40:100 to obtain a mineralizer;
[0048] (4) A dissolution accelerator is prepared by mixing 25 parts of a grinding aid, 25 parts of a decomposition promoter, 20 parts of a mineralizer and 65 parts of water.
[0049] The prepared dissolution accelerator is used in the calcination preparation of cement clinker, and the method is as follows:
[0050] (1) Raw material powder (white raw material) is taken into the kiln and dried at 105° C. for 1 hour. The melting accelerator is added to the white raw material at a rate of 1.1 wt‰ of the white raw material and mixed evenly to obtain raw material powder to be fired. The chemical composition of the white raw material is shown in Table 1.
[0051] (2) The raw material powder to be fired is pressed into cement raw material test blocks, dried, and then moved into a high temperature furnace and calcined at 950°C for 20 minutes. Then, it is quickly moved into a high temperature furnace and calcined at 1430°C for 30 minutes to obtain cement clinker.
[0052] Comparative Example 1: The rest is the same as Example 1, except that:
[0053] In step (1), sodium glucoheptonate was not added.
[0054] Comparative Example 2: The rest is the same as Example 1, except that:
[0055] The sodium glucoheptonate in step (1) is replaced by sodium gluconate.
[0056] Comparative Example 3: The rest is the same as Example 1, except that:
[0057] The decomposition accelerator in step (4) is replaced with water.
[0058] Comparative Example 4: The rest is the same as Example 1, except that:
[0059] The silver acetate in step (2) was replaced by silver nitrate.
[0060] Comparative Example 5: The rest is the same as Example 1, except that:
[0061] Silver hexafluoroantimonate was replaced by silver fluoride.
[0062] Comparative Example 6: The rest is the same as Example 1, except that:
[0063] No silver acetate or silver hexafluoroantimonate was added, and only sodium nitrate was used as a decomposition promoting agent.
[0064] Comparative Example 7: The rest is the same as Example 1, except that:
[0065] No silver acetate and sodium nitrate were added, and only silver hexafluoroantimonate was used as a decomposition promoting agent.
[0066] Comparative Example 8: The rest is the same as Example 1, except that:
[0067] Without adding silver hexafluoroantimonate and sodium nitrate, only silver acetate will serve as a decomposition promoting agent.
[0068] Comparative Example 9: The rest is the same as Example 1, except that:
[0069] Apatite is used to replace the dissolution accelerator to prepare the raw meal powder to be fired.
[0070] Comparative Example 10: The rest is the same as Example 1, except that:
[0071] Apatite is used to replace the dissolution accelerator, and 0.75wt% of the apatite is added to the white raw meal to obtain raw meal powder to be fired.
[0072] In order to test the performance of the dissolution accelerator, in the process of calcining and preparing cement clinker in Examples 1-3 and Comparative Examples 1-10, each ash dish was filled with 1.0000g±0.0050g of the mixed raw material powder to be burned, and after being evenly spread, it was calcined at 750°C and 820°C for 30min respectively, and its ignition loss was measured. The blank group used water to replace the dissolution accelerator. The results are shown in Table 2:
[0073] Table 2 Loss on ignition test results
[0074]
[0075]
[0076] The raw meal powders to be fired prepared in Examples 1-3 and Comparative Examples 1-10 were pressed into cement raw meal test blocks and dried, then moved into a high temperature furnace and calcined at 950°C for 30 minutes, and then quickly moved into a high temperature furnace and calcined at 1400°C and 1430°C. The blank group used water to replace the dissolution accelerator. The free calcium oxide content of each group was measured. The results are shown in Table 3:
[0077] Table 3 Burnability test results
[0078]
[0079] The setting time of the cement clinker prepared in Examples 1-3 and Comparative Examples 1-10 was determined as follows:
[0080] According to GB / T 21372-2024 Portland Cement Clinker, the blank group used water to replace the dissolution accelerator, and the results are as follows:
[0081] Table 4 Test results of setting time of cement clinker
[0082]
[0083]
[0084] As can be seen from the results of Tables 2-4, the ignition loss and ignition ease of Comparative Examples 1 and 2 are significantly lower than those of Example 1, indicating that after replacing or omitting sodium glucoheptonate in the melting promoter, no good calcination promotion effect can be obtained. Only when sodium glucoheptonate is added, the melting promoter can have a higher calcination promotion performance. Comparative Example 1 also reflects that the traditional grinding aid does not have a good calcination promotion effect. The ignition loss and ignition ease of Comparative Example 3 are also significantly lower than those of Example 1, indicating that the grinding aid containing sodium glucoheptonate relies on the decomposition agent to exert its calcination promotion effect.
[0085] The ignition loss and ignition ease of comparative examples 4-8 are significantly lower than those of example 1, indicating that only when silver acetate, silver hexafluoroantimonate and sodium nitrate are used in combination can they synergistically exert an efficient decomposition promoting effect, and none of the three can be missing. Once replaced by other analogs, the performance of the melting promoter will be greatly reduced. In addition, the effect of using silver acetate, silver hexafluoroantimonate or sodium nitrate alone as a decomposition promoting agent is poor, which is significantly lower than the effect of using the three in combination.
[0086] In Comparative Examples 9 and 10, conventional phosphate mineralizers were used as additives to calcine and prepare cement clinker. In Comparative Example 9, due to the small amount of apatite used, its ignition loss and burnability were significantly lower than those in Example 1, and apatite delayed the initial setting and final setting time of cement clinker. In Comparative Example 10, excessive apatite was added to improve ignition loss and burnability. Although the effects of ignition loss and burnability were close to those of Example 1, excessive apatite caused the initial setting and final setting time of cement clinker to be further delayed. It can be seen that the present invention further solves the application difficulties and existing problems of traditional phosphorus-containing mineralizers.
Claims
1. A melting accelerator, characterized in that The invention comprises the following components in parts by weight: 10-25 parts of a grinding aid, 15-25 parts of a decomposition promoter, 10-20 parts of a mineralizer, and 30-65 parts of water; the grinding aid comprises at least two of polyether polyol, polyglycerol and sodium glucoheptonic acid, and the decomposition promoter comprises at least two of silver acetate, silver hexafluoroantimonate and sodium nitrate.
2. The melting accelerator according to claim 1, characterized in that The mineralizer comprises at least one of zinc sulfate and sodium hypochlorite.
3. The melting accelerator according to claim 2, characterized in that The mineralizer consists of zinc sulfate and sodium hypochlorite in a mass ratio of 20-40:40-100.
4. The melting accelerator according to claim 1, characterized in that The grinding aid consists of polyether polyol, polymerized glycerol and sodium glucoheptonate in a mass ratio of 20-40:30-70:5-35.
5. The melting accelerator according to claim 1, characterized in that The decomposition promoting agent is composed of silver acetate, silver hexafluoroantimonate and sodium nitrate in a mass ratio of 25-55:10-30:20-60.
6. The method for preparing the melting accelerator according to any one of claims 1 to 5, characterized in that: The steps include: (1) a grinding aid is prepared by mixing polyether polyol, polyglycerol and sodium glucoheptonic acid; a decomposition promoter is prepared by mixing silver acetate, silver hexafluoroantimonate and sodium nitrate; and a mineralizer is prepared by mixing zinc sulfate and sodium hypochlorite; (2) A dissolution accelerator is prepared by mixing a grinding aid, a decomposition promoter, a mineralizer and water in proportion.
7. Use of the dissolution accelerator according to any one of claims 1 to 5 in cement clinker burning.
8. The use according to claim 7, characterized in that: The steps include: (1) adding the dissolution accelerator into cement raw meal to obtain raw meal powder to be burned; (2) The raw material powder to be burned is calcined to obtain cement clinker.
9. The use according to claim 8, characterized in that: In step (1), the amount of the dissolution accelerator added is 1.0-1.2wt‰ of the cement raw material, and the cement raw material is dried white raw material.
10. The method for preparing the crack self-repairing cement-based material according to claim 8, characterized in that: In step (2), the calcination conditions are calcination at 750-820°C for 15-45 minutes, and then heating to 1400-1430°C for calcination for 30-60 minutes.
Citation Information
Patent Citations
Reinforced cement grinding aid
CN106082755A
Composite liquid raw material mineralizer
CN115353307A
Preparation and application of composite raw material melting accelerant
CN118459125A
Fluxes / Mineralizers for calcium sulfoaluminate cements
EP2842922A1
Fluxes / mineralizers for calcium sulfoaluminate cements
IN201617004396A